Mycophenolate mofetil versus cyclophosphamide for idiopathic membranous nephropathy; a double blind and randomized clinical trial - Fatemeh Hayati; Heshmatollah Shahbazian; Ali Ghorbani; Shahla Ahmadi Halili; Eisa Rezaei; Leila Sabetnia; Seyed Seifollah Beladi Mousavi (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: The current treatment regimens for patients with idiopathic membranous nephropathy (MN) are based on cyclophosphamide-glucocorticoid or calcineurin inhibitor-glucocorticoid. Objectives: We evaluated whether mycophenolate mofetil (MMF) -glucocorticoid could be an option for first-line therapy among these patients. Patients and Methods: In a double-blinded, randomized and controlled clinical trial, we compared the effect of MMF with cyclophosphamide in inducing complete or partial remission (PR) among patients with nephrotic syndrome due to idiopathic MN. All of the patients in both groups also received steroid, renin-angiotensin blockers and statins. Diuretics were also used in the patients who had edema. The primary end point of our study was change in urinary protein/creatinine ratio. Results: A total of 30 patients completed the study. Around 17 patients received MMF (2 g/d) and 13 patients received intravenous or oral cyclophosphamide for 6 months. At the start of the study, no significant differences in demographic and biochemical parameters of patients including the urinary protein excretion rate between two groups (P = 0.432). The proportion of proteinuria was 5235 ± 1655 mg/24 in MMF group and 8781 ± 8741 mg/24 in the cyclophosphamide group at the beginning of the study. The rate of complete and PR were 5.9% and 52.9 in MMF group versus 16.7% and 100% in cyclophosphamide group which it is significantly lower in MMF group. Kidney function was stable in both groups during treatment. Conclusions: According to the result of our study, a 6-month therapy with MMF-glucocorticoid is not recommended for treatment of patients with nephrotic syndrome due to idiopathic MN.